Negafibonacci numbers?

The Fibonacci numbers are given by

  • F ( 0 ) = 0 F(0) = 0
  • F ( 1 ) = 1 F(1) = 1
  • F ( n ) = F ( n 1 ) + F ( n 2 ) . F(n) = F(n-1) + F(n-2).

So, the first few are 0 , 1 , 1 , 2 , 3 , 5 , 8 , 13. 0, 1, 1, 2, 3, 5, 8, 13.

If we generalize this to negative numbers, what is F ( 8 ) ? F(-8)?


The answer is -21.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Geoff Pilling
Nov 28, 2016

In general,

F ( n ) = F ( n 1 ) + F ( n 2 ) F(n) = F(n-1) + F(n-2)

so you can calculate backwards by saying:

F ( n 2 ) = F ( n ) F ( n 1 ) F(n-2) = F(n) - F(n-1)

This gives,

  • F ( 1 ) = 1 F(-1) = 1
  • F ( 2 ) = 1 F(-2) = -1
  • F ( 3 ) = 2 F(-3) = 2
  • F ( 4 ) = 3 F(-4) = -3
  • F ( 5 ) = 5 F(-5) = 5

And in general,

F n = ( 1 ) n + 1 F n F_{-n}=(-1)^{n+1}F_{n}

Here is a quick proof by induction...

Consider postive n n .

Its trivially true for n = 0 -n = 0 and n = 1 -n = -1 . Assume its true for F n + 1 F_{-n+1} and F n + 2 F_{-n+2} , and we will show its true for F n F_{-n}

  • F n = F n + 1 F n + 2 F_{-n} = F_{-n+1} - F_{-n+2} (as we saw above)

  • F n = ( 1 ) n F n 1 ( 1 ) n + 1 F n 2 F_{-n} = (-1)^{n}F_{n-1} - (-1)^{n+1}F_{n-2}

  • F n = ( 1 ) n + 1 ( F n 1 + F n 2 ) F_{-n} = (-1)^{n+1}(F_{n-1} + F_{n-2})

  • F n = ( 1 ) n + 1 F n F_{-n} = (-1)^{n+1}F_n

  • QED

So,

F ( 8 ) = F ( 8 ) = 21 F(-8) = -F(8) = \boxed{-21}

F n = ( 1 ) n + 1 F n F_{-n}=(-1)^{n+1}F_{n}

Is this true for all integers n n ?

Pi Han Goh - 4 years, 6 months ago

Log in to reply

Seems to be; no formal proof but I am 99.9999% sure :P

Yatin Khanna - 4 years, 6 months ago

Log in to reply

Yes, its true... Proof by induction...

Consider postive n n .

Its trivially true for n = 0 -n = 0 and n = 1 -n = -1 . Assume its true for F n + 1 F_{-n+1} and F n + 2 F_{-n+2} , and we will show its true for F n F_{-n}

  • F n = F n + 1 F n + 2 F_{-n} = F_{-n+1} - F_{-n+2} (as we saw above)

  • F n = ( 1 ) n F n 1 ( 1 ) n + 1 F n 2 F_{-n} = (-1)^{n}F_{n-1} - (-1)^{n+1}F_{n-2}

  • F n = ( 1 ) n + 1 ( F n 1 + F n 2 ) F_{-n} = (-1)^{n+1}(F_{n-1} + F_{n-2})

  • F n = ( 1 ) n + 1 F n F_{-n} = (-1)^{n+1}F_n

  • QED

Geoff Pilling - 4 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...